2013
DOI: 10.1016/j.nlm.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin–proteasome system as a critical regulator of synaptic plasticity and long-term memory formation

Abstract: Numerous studies have supported the idea that de novo protein synthesis is critical for synaptic plasticity and normal long-term memory formation. This requirement for protein synthesis has been shown for several different types of fear memories, exists in multiple brain regions and circuits, and is necessary for different stages of memory creation and storage. However, evidence has recently begun to accumulate suggesting that protein degradation through the ubiquitin–proteasome system is an equally important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 118 publications
2
97
0
1
Order By: Relevance
“…Although the molecular mechanisms underlying the reconsolidation process have only begun to be elucidated, a number of recent studies have focused on changes in ubiquitin-proteasome activity and AMPA receptor subunit exchange as potential regulators of memory reconsolidation (reviewed in, Jarome and Helmstetter, 2013a). For example, inhibition of proteasome activity prevents the initiation of the reconsolidation process Jarome et al, 2011) and can prevent reconsolidation-dependent memory strengthening (Lee, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms underlying the reconsolidation process have only begun to be elucidated, a number of recent studies have focused on changes in ubiquitin-proteasome activity and AMPA receptor subunit exchange as potential regulators of memory reconsolidation (reviewed in, Jarome and Helmstetter, 2013a). For example, inhibition of proteasome activity prevents the initiation of the reconsolidation process Jarome et al, 2011) and can prevent reconsolidation-dependent memory strengthening (Lee, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is unlikely that we would see reduced freezing if our manipulation disrupted reconsolidation. Blocking NMDA receptors prevents memory destabilization (Ben Mamou et al 2006), effectively blocking the initiation of reconsolidation (Johansen et al 2011;Jarome and Helmstetter 2013). Therefore, if intra-IL APV primarily affected reconsolidation, higher freezing would be anticipated, as the original fear memory would persist.…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala is a critical site of plasticity for the formation of fear memories in the brain (LeDoux 2000). Consistent with this, inhibiting gene transcription, protein synthesis, and protein degradation in the amygdala impairs fear memory consolidation following behavioral training (Bailey et al 1999;Parsons et al 2006;Jarome et al 2011) leading to the theory that a coordinated regulation of changes in gene transcription in the amygdala is necessary for the formation of fear memories (Johansen et al 2011;Jarome and Helmstetter 2013). However, although some studies have suggested a role for posttranslational modification of histone mediated chromatin remodeling in the consolidation of fear memories in the amygdala (Koshibu et al 2009;Monsey et al 2011;Mahan et al 2012), it is unknown if histone lysine methylation is required for lateral amygdala (LA)-dependent fear memory consolidation.…”
mentioning
confidence: 91%